Solved problems in classical electrodynamics and theory of relativity - Radu, Daniel; Merches, Ioan (CRC Press, an imprint of Taylor & Francis Group, LLC, 2023)
"This book is intended for undergraduate and graduate students in physics, engineering, astronomy, applied mathematics and for researchers working in related subjects. It is an excellent study tool for those students who would like to work independently on more electrodynamics problems in order to deepen their understanding and problem solving skills. The book discusses main concepts and techniques related to Maxwell's equations, potentials and fields (including Liénard-Wiechert potentials), electromagnetic waves, and the interaction and dynamics of charged point particles. It also includes content on magnetohydrodynamics and plasma, radiation and antennas, special relativity, relativistic kinematics, relativistic dynamics and relativistic-covariant dynamics and general theory of relativity. It contains a wide range of problems, ranging from electrostatics and magnetostatics to the study of the stability of dynamical systems, field theories and black hole orbiting. The book even contains interdisciplinary problems from the fields of electronics, elementary particle theory, antenna design. Detailed, step-by step calculations are presented, meeting the need for a thorough understanding of the reasoning and steps of the calculations by all students, regardless of their level of training. Additionally, numerical solutions are also proposed and accompanied by adjacent graphical representations and even multiple methods of solving the same problem. It is structured in a coherent and unified way, having a deep didactic character, being thus oriented towards a university environment, where the transmission of knowledge in a logical, unified and coherent way is essential. It teaches students how to think about and how to approach solving electrodynamics problems. - Contains a wide range of problems and applications from the fields of electrodynamics and the theory of special relativity. - Presents numerical solutions to problems involving nonlinearities. - Details command lines specific to Mathematica software dedicated to both analytical and numerical calculations, which allows readers to obtain the numerical solutions as well as the related graphical representations"--Provided by publisher.